PENGARUH BAHASA IBU TERHADAP PENGGUNAAN BAHASA INDONESIA PADA PIDATO PERSUASIF DI SMP NEGERI 2 BATUJAJAR - Yoki N Kusmawanto; Indrie Destyanie Ferdian; Heri Isnaini (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Language makes the conditions used by humans to think in communication activities, one of them is speech. The research here aims to determine the influence of mother tongue on the use of Indonesian in a persuasive speech at SMP Negeri 2 Batujajar. The reason the researchers made this title is because currently the function of the Indonesian language is not considered important for some students. The research method used is a qualitative method, with an investigative approach because researchers usually collect data. The use of Indonesian in the persuasive speeches of students at Batujajar Public Middle School 2 was apparently colored by the influence of mother tongue or everyday language. From the results of the research, 30 people who were persuasive in their speech turned out that there were 10 people giving speeches using mother tongue and there were 20 people who used Indonesian. It can be stressed that students who have persuasive speech using mother tongue are 33.4% and those who use Indonesian are 66.6%. The use of mother tongue that occurs is caused by several factors, namely factors from the family environment, the playing environment, and the environment in the school so that students are more accustomed to using mother tongue than using Indonesian.